Coronavirus Infection in Children (Situation on February 2020) - Leyla S. Namazova-Baranova; Alexandr A. Baranov (Педиатрическая фармакология, 2020)
Considering the raft of information about the coronavirus infection in the Internet most of which cannot be considered not only as evidence-based medicine but even as proven or scientific, we are going to perform analysis of published literature and present you all the up-to-date data on coronavirus infection in the world in our journal in every issue.